2019
DOI: 10.3390/ani10010068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Culture (Saccharomyces cerevisiae) on Broilers: A Preliminary Study on the Effective Components of Yeast Culture

Abstract: This study was aimed at determining the effective ingredients of yeast culture (YC) for animal breeding. First, the contents of YCs obtained from various fermentation times were detected using gas-chromatography. A total of 85 compounds were identified. Next, 336 Arbor Acres (AA) broilers were randomly divided into seven experimental groups and fed a basal diet, diets supplemented with YCs obtained at various fermentation times, or SZ1 (a commercial YC product). A significant increase in body weight gain (BWG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
(54 reference statements)
0
17
1
Order By: Relevance
“…Severe damage to organs has been eliminated due to diets that may contain these toxins in the presence of S. cerevisiae for their ability to reduce animal stress, providing vitamins, enzymes, and proteins (Baptista et al, 2005). Saccharomyces cerevisiae in calf diets augment immunological effect by increasing IgM and IgA activity against pathogens, enhancing intestinal development and function, adsorb mycotoxins, modulate gut microbiota, and reduce post-weaning diarrhea (Qamar et al, 2001;Sun et al, 2019;Elghandour et al, 2020). We found that the increased abundance of Saccharomyces in group T3 improved the concentrations of IgA and IgG than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Severe damage to organs has been eliminated due to diets that may contain these toxins in the presence of S. cerevisiae for their ability to reduce animal stress, providing vitamins, enzymes, and proteins (Baptista et al, 2005). Saccharomyces cerevisiae in calf diets augment immunological effect by increasing IgM and IgA activity against pathogens, enhancing intestinal development and function, adsorb mycotoxins, modulate gut microbiota, and reduce post-weaning diarrhea (Qamar et al, 2001;Sun et al, 2019;Elghandour et al, 2020). We found that the increased abundance of Saccharomyces in group T3 improved the concentrations of IgA and IgG than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast-derived products, such as yeast cell call ( Wang et al., 2017 ; Ma et al., 2020 ), yeast hydrolysate ( Fu et al, 2019 ; Rahimnejad et al., 2020 ), dried yeast extracts ( Kim et al., 2019b ), and yeast culture ( Samarasinghe et al, 2004 ; Sun et al., 2020 ), are natural feed additives that have been used in animals for decades. Supplementing animals with yeast cell wall improved the growth performance, digestive function, and antioxidant capacity of animals ( Li et al., 2016 ; Wang et al., 2017 ; Salinas-Chavira et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing animals with yeast cell wall improved the growth performance, digestive function, and antioxidant capacity of animals ( Li et al., 2016 ; Wang et al., 2017 ; Salinas-Chavira et al., 2018 ). Yeast culture contains cell wall and various metabolites, which have been proposed to stimulate bacterial growth in the digestive tract and optimize animal feed intake to improve growth performance as well as active the natural killer cells and B lymphocytes to promote immune function ( Gao et al., 2008 ; Sun et al., 2020 ). The addition of yeast culture could improve intestinal nutrients digestibility ( Samarasinghe et al., 2004 ), enhance disease resistance ( Bu et al., 2019 ), and alleviate inflammatory responses ( Bu et al., 2020 ) in animals.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancements due to 0.2 and 0.3g SC/kg addition as compared to control groups were 35.6 and 47.3%, respectively. Comparative findings have been showed by Sun et al (2020) and Al-Khalaifa et al (2019) on treated broilers with dietary addition of SC and SB, respectively. On the opposite, Khobondo et al (2015) decided that dietary probiotic addition didn't significantly affect the levels of IgM level.…”
Section: Serum Immunoglobulinsmentioning
confidence: 99%
“…One of the most popular probiotic products contain Sacharomcyces spp varieties and has long been fed to poultry, is Saccharomyces cerevisiae (SC) which produce from malted grains fermentation also known as ''baker's yeast'' (Khan et al, 2014). Dietary SC supplements significantly influence blood haematology and biochemical indices which could be utilized to evaluate the pathological and nutritional responses of broiler (Sun et al, 2020). A research by Haghighi et al (2006) recommended that SC have an immune boosting effect due to improve acceptance of natural antibodies in chickens.…”
Section: Introductionmentioning
confidence: 99%